The Affordable Care Act and Ambulance Response Times - Charles Courtemanche; Andrew I. Friedson; Andrew P. Koller; Daniel I. Rees (Institute of Labor Economics (IZA), 2017)
This study contributes to the literature on supply-side adjustments to insurance expansions by examining the effect of the Affordable Care Act (ACA) on ambulance response times. Exploiting temporal and geographic variation in the implementation of the ACA as well as pre-treatment differences in uninsured rates, we estimate that the expansions of private and Medicaid coverage under the ACA combined to slow ambulance response times by an average of 19%. We conclude that, through extending coverage to individuals who, in its absence, would not have availed themselves of emergency medical services, the ACA added strain to emergency response systems.
Keywords: I11; I13; I18; 330; Affordable Care Act; ambulance; health insurance; health care capacity; health care workforce